The Future of Virtual Banking in Malaysia - Shahrul Nizam Salahudin,; Chew Fong Joo, (Research in Management of Technology and Business, 2022)
Virtual bank is the digitization of all traditional banking operations and services that were previously available to consumers when they visited a bank branch. Virtual banks are more complex and sophisticated because every banking activity, process, and stage of providing banking products and services will involve technology. This research aims to identify the issues, challenges and trends of virtual banking in Malaysia and to study the future scenario of virtual banking in Malaysia. This study uses the STEEPV analysis to identify the issue, trends and challenges of virtual banking in Malaysia. The questionnaire will used as the research instrument by distributing the questionnaire to the Gen Y online banking user in Malaysia. The sample size is 384 respondents with the response rate of 31.25%. The findings will be analysed by using SPSS software. Impact-uncertainty analysis and scenario analysis are used to study the future scenario of virtual banking in Malaysia. The result of top two issues, challenges and trends are efficient and effective services and ensure data privacy and security. The four scenarios building that has been constructed from the top two issues, challenges and trends. The best scenario of this research is emergence of new bank. This research will help the virtual banking user and developer have better understanding and outlook toward the virtual banking